POLA PERTANIAN TERPADU TERNAK DAN TANAMAN HORTIKULTURA DI KOTA PEKANBARU - Latifa Siswati (Jurnal Peternakan, 2012)
On integrated faming sistem which includes the provision of necessary technology types/varietas, various. Relatively favorable economic value commodities such as food crops, horticulture, livestock. Riset objectives are ; to know integrated farming sistem, to know integrated variation applied by the farmers, to see farm of diversity and farmers income. Responden is family of farmer owning horticulture, livestock. Research method used is survey. The result integrated farming sistem; A. horticulture; vegetable and cattle, corn and catlle. B. fruits and cattle;pepaya,melon and catlle, water melon and cattle. C. horticulture and goat; vegetable and goat. D. fruit and chicken; pepaya and chicken. Pattern of integrated farming sistem was 21 cattle ,12 goat, 0,42 ha horticulture. Increase income Rp 3.961,425,- per month